2015
DOI: 10.1080/02673037.2015.1025372
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of the Usage and Affective Experience of the Residential Environment to Residential Satisfaction

Abstract: The existing literature has documented that housing conditions, neighborhood characteristics, and socioeconomics are important determinants of residential satisfaction. However, the contribution of the actual usage of the residential environment to residential satisfaction has rarely been studied. To help fill in this gap, this study examines the contribution of the usage of housing and neighborhoods as well as the affective residential experience to residential satisfaction. We apply a subjective well-being f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 44 publications
5
70
0
10
Order By: Relevance
“…In essence, this study shows interesting linkages between satisfaction of neighbourhood quality and residential mobility behaviour. The study findings reflect good dimensions of residential satisfaction ranging from the micro context of the dwelling to the macro-setting of the neighbourhood ( Aragonés, Amérigo, & Pérez-López, 2016;Mohit & Adel Mahfoud, 2015;Wang & Wang, 2015). This study has also revealed significant relationships between residential satisfaction measurements based on residents' perceptions, and residential mobility behaviours.…”
supporting
confidence: 61%
“…In essence, this study shows interesting linkages between satisfaction of neighbourhood quality and residential mobility behaviour. The study findings reflect good dimensions of residential satisfaction ranging from the micro context of the dwelling to the macro-setting of the neighbourhood ( Aragonés, Amérigo, & Pérez-López, 2016;Mohit & Adel Mahfoud, 2015;Wang & Wang, 2015). This study has also revealed significant relationships between residential satisfaction measurements based on residents' perceptions, and residential mobility behaviours.…”
supporting
confidence: 61%
“…Mohit and Mahfoud [30] found that elements of DI, especially floor area, correlate positively with residential satisfaction with public housing in Kuala Lumpur, Malaysia, where dwelling size was found to be an important predictor of residential satisfaction. Dwelling size was also found to be an important predictor of residential satisfaction in the works of Ibem and Aduwo [31], Ibem and Amole [32,33] in the Nigerian context, Buys and Miller [25] in the Australian context, and Wang and Wang [34] in the Chinese context. Larger dwelling size may improve residential satisfaction [35,36].…”
Section: Dwelling Characteristicsmentioning
confidence: 86%
“…Various studies on housing focus on access to public facilities such as public transportation, schools, police stations, healthcare facilities, markets and food stalls [26,27,30,34,37,39,44,[48][49][50]. According to Huang and Du [39], in their study in China, public facilities have a significant influence on residential satisfaction.…”
Section: Public Facilitiesmentioning
confidence: 99%
“…Location The traditional adage of 'location, location, location' resonates with the parameters of saleability, high appreciation and residential satisfaction (Alias et al 2011;Chuan et al 2012;Wang & Wang 2015). Unsurprisingly, projects that are closer to desirable facilities are deemed to be more attractive and have less risk associated with them in terms of sales and loan assurance (Ibem & Amole 2013;Ponomareva 2012).…”
Section: Product Characteristicsmentioning
confidence: 99%